Journal of the Iranian Chemical Society - Shamsipur, M.; Saboury, Ali Akbar; SpringerLink (Online service) (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: Springer.)
JICS is an international journal covering general fields of chemistry. JICS welcomes high quality original papers in English dealing with experimental, theoretical and applied research related to all branches of chemistry. These include the fields of analytical, inorganic, organic and physical chemistry as well as the chemical biology area. Review articles discussing specific areas of chemistry of current chemical or biological importance are also published. JICS ensures visibility of your research results to a worldwide audience in science. You are kindly invited to submit your manuscript to the Editor-in-Chief or Regional Editor. All contributions in the form of original papers or short communications will be peer reviewed and published free of charge after acceptance.
Keywords: Analytical chemistry; Inorganic chemistry; Organic chemistry; Physical chemistry; Biochemistry; Analytical Chemistry; Inorganic Chemistry; Physical Chemistry; Biochemistry, general; Organic Chemistry